CORE STABILITY EXCERCISE LEBIH BAIK DIBANDINGKAN MCKENZIE EXCERCISE DALAM PENURUNAN DISABILITAS PASIEN NON-SPECIFIC LOW BACK PAIN - Ganesa Puput Dinda Kurniawan; I Made Muliarta; Sugijanto -; I Made Ady Wirawan; Susy Purnawati; Wahyudin - (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Non-specific low back pain is the symptom of lower back pain that occurs without an obvious cause, the diagnosis is based on exclusion of specific pathology. Non-specific low back pain can result in pain, muscle spasm and muscle imbalance, it can decrease the stability of the abdominals and lower back, limitation in lumbar mobility , changes posture, and it’s couse make disability in patients with non-specific low back pain. Exercise therapy for non-specific low back pain is high recommend to increased stability and correct posture of the spine, for this case thsth can be used for exercise therapy is like McKenzie exercises and core stability exercise. The purpose of this study is to determine the core stability excercise better than McKenzie excercise for release in reduce patient disability in non-specific low back pain. This research applied experimental research method with Pre and Post Test Control Group Design. The research was conducted in Dr Soeradji Tirtonegoro Klaten. There were 32 subjects taken for this research. Disability was measured by oswestry disability index (ODI) before and after treatment. They were divided into two treatment groups consisting of core stability 16 subject for the Mckenzie exercise is 16 and the frequens are 2 times a weak in a month. Statistical test results obtained, have a decline ODI score at the first group have done with a value of p = 0.000 and the second gorup with p = 0.000. it means that both of the group are significantly improve functional activity. From the comparative test data by t-test using the data difference in both groups p value <0.05, which means indicated that there is a significant difference. Therefore, the conclusion of this research indicated thar the core stability excercise better than McKenzie excercise for release in reduce patient disability in non-specific low back pain. The study is expected to benefit in patients with non-specific low back pain in reducing disability.